Husbands’ Resistance to Family Planning: A Mubādalah Study of Urban and Rural Muslim Families in Indonesia - Indrawati Imron (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This study examines husbands’ resistance to the Family Planning (Keluarga Berencana, KB) program and its implications for family well-being. It aims to analyze the underlying factors driving opposition to family planning and to assess their consequences for spousal relations and household welfare. Employing a qualitative approach, data were collected through in-depth interviews and participant observation involving ten primary informant husbands who opposed family planning in the cities of Bandar Lampung and Metro (urban contexts) as well as in Pesawaran and Pringsewu Regencies (rural contexts) and health practitioners. The mubādalah theory was employed as an analytical framework to evaluate reciprocity and gender justice in family decision-making processes. The findings indicate that resistance to family planning was shaped by religious beliefs, socio cultural norms, psychological factors and perceptions of masculinity, as well as economic and educational considerations. In urban settings, resistance tended to be driven primarily by economic calculations, social stigma, and concerns regarding contraceptive side effects. By contrast, in rural areas it was largely influenced by lower levels of education, limited access to health services, and traditional beliefs that regard having many children as a source of sustenance and blessing. Recommendations require strengthening gender-equity-based family planning education, active involvement of men, and health service policies.